First record of the genus Trilacuna Tong & Li, 2007 (Araneae, Oonopidae) from Xizang, China, with descriptions of three new species and one newly recorded species - Songlu Shi; Dongju Bian; Yanfeng Tong; Shuqiang Li (ZooKeys)
Four species of the genus Trilacuna Tong & Li, 2007 from Xizang, China are recognized, including three new species and one newly recorded species: T. bangla Grismado & Ramírez, 2014, T. mainling Tong & Li, sp. nov. (♂♀), T. metok Tong & Li, sp. nov. (♂♀) and T. zayu Tong & Li, sp. nov. (♂♀). Descriptions, diagnoses and photomicroscopy images are provided.